I have a feeling it's
3/(x+1) - (1/2) = 1/(3x+3)
for the problem, I'm just trying to figure it out :o
if 1/3x is (1/3)x then...
okay so first move the x's to one side and the numbers to the other: (3/x) - (1/3)x = 3-1 +1/2
simplify: (3/x) - (1/3)x = 5/2
multiply everything by x: 3-(1/3)x^2=(5/2)x
move: 0= (1/3)x^2 + (5/2)x -3
now use the quadratic formula to solve for x.
ok i think it is written like this 3/1x+1=1/3x+3
make the number to one side and the variable to another side
3/1x-1/3x= -1 +3
8/3 x = 2
u can multiply the nominators by 3 which will give u the equation like this
8x = 6
x = 3/4
hope this help u
This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.
More Questions & Answers...